Automorphic Forms and Holomorphic Functions on the Upper Half-plane - Alam, Md Shafiul (GANIT: Journal of Bangladesh Mathematical Society, 2023)
We define a set of holomorphic functions in terms of the Hauptmodul of a quotient Riemann surface and prove that these functions are holomorphic on the upper half-plane. It is also shown that these functions are automorphic forms of weight k with respect to a Fuchsian group. GANIT J. Bangladesh Math. Soc. 43.1 (2023) 036- 044